(untitled) (Conference Zone, 2022)
Today’s in the day children of disability for the reason the first next - spiritual disorders (29.2%), the second instead - nerve _ _ system diseases (26.5%), the third o ’ rinda and - birth _ _ had defects (23.3 % ) . children enters _ In all age groups, boys are the leaders in children’s disabilities (58%). Disability among boys is 1.2-1.7 times higher than among girls. Among disabled children diagnosed with cerebral palsy (BMF), psychoneurological deficits are in the first place, and about 70% of them have various speech disorders.